Peningkatan Hasil Belajar Bilangan Romawi melalui Model Kooperatif Tipe Make A Match Peserta Didik Kelas IV SD Negeri Malangsari Tahun Pelajaran 2017/2018 - Dewi Pujiyani (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
This research is motivated by the low learning outcomes of Mathematics in Roman numerals caused by several factors: 1) the inaccurate use of learning methods, 2) the lack of use of learning media, 3) the lack of active students during learning. Therefore, research is needed to improve student learning outcomes. This research uses Classroom Action Research (CAR) with steps 1) planning, 2) implementation, 3) observation, 4) reflection. This CAR will implement a make a match type cooperative model which is carried out with two learning cycles. This study uses quantitative data analysis techniques from the results of observations of teacher ability and student activity and student evaluation tests. This research was successfully carried out with evidence of prasiklus activities of student learning outcomes only by 18.18%, up in cycle 1 by 90.9% and increasing in cycle 2 by 100%. The classical average value in the pre-cycle only reached 41.18, increasing significantly in cycle 1 of 77.91 and increasing again in cycle 2 of 82.5.